Effects of ad libitum and restricted diets in different feeding regimes on growth and carcass attributes of boars of a selected genetic line - Jansen van Rensburg, Christine (University of Pretoria, 2013)
Dissertation (MSc(Agric))--University of Pretoria, 2010.